2020
DOI: 10.1002/jlb.3a0820-207r
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil recruitment by chemokines Cxcl1/KC and Cxcl2/MIP2: Role of Cxcr2 activation and glycosaminoglycan interactions

Abstract: Chemokines play a crucial role in combating microbial infection by recruiting blood neutrophils to infected tissue. In mice, the chemokines Cxcl1/KC and Cxcl2/MIP2 fulfill this role. Cxcl1 and Cxcl2 exist as monomers and dimers, and exert their function by activating the Cxcr2 receptor and binding glycosaminoglycans (GAGs). Here, we characterized Cxcr2 G protein and-arrestin activities, and GAG heparan sulfate (HS) interactions of Cxcl1 and Cxcl2 and of the trapped dimeric variants. To understand how Cxcr2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 73 publications
4
55
0
Order By: Relevance
“…Both CXCL1 and CXCL2 can be secreted by monocytes and neutrophils at the site of inflammation. They function through the chemokine receptor CXCR2 to act as chemotactic agents for leukocytes and hematopoietic cells (Sawant et al, 2020).…”
Section: Xbj and C0127s Directly Or Indirectly Attenuate Cytokine Storm To Protect Cardiac Function And Improve Survival In Septic Shockmentioning
confidence: 99%
“…Both CXCL1 and CXCL2 can be secreted by monocytes and neutrophils at the site of inflammation. They function through the chemokine receptor CXCR2 to act as chemotactic agents for leukocytes and hematopoietic cells (Sawant et al, 2020).…”
Section: Xbj and C0127s Directly Or Indirectly Attenuate Cytokine Storm To Protect Cardiac Function And Improve Survival In Septic Shockmentioning
confidence: 99%
“…Cxcl1 (also known as mouse CXCL1/mCXCL1 and KC) and Cxcl2 (also known as mouse CXCL2/mCXCL2 and MIP2) are the major chemokines that orchestrate neutrophil recruitment in mice (18)(19)(20). We have previously shown that Cxcl1 and Cxcl2 dimers bind GAGs with higher affinity and that their GAG interactions and neutrophil recruitment profiles are different (29,30). Our current study indicates that Cxcl1 and Cxcl2 form a heterodimer with a propensity comparable to homodimers.…”
Section: Introductionmentioning
confidence: 64%
“…We used a ~9 kDa HS (Iduron) and a ~15 kDa heparin (Calbiochem). The GAGs were biotinylated using the EZ-Link Biotin LC Hydrazide reagent, immobilized to a Sensor Chip SA, and binding measurements were carried out as described (30). We used two different chips -one containing ~80 RU of immobilized GAG defined as a lowdensity chip and the other ~220-250 RU of immobilized GAG defined as a high-density chip.…”
Section: Structural Model Of the Heterodimermentioning
confidence: 99%
“…However, viral clearance from the skin was similar in control DTA mice and Nav 1.8 -DTA mice, excluding the possibility of the larger lesions in nociceptor-deficient mice being due to uncontrolled viral replication. This phenotype was associated with higher levels of chemokines and inflammatory cytokines, including CXCL1, which is known to attract neutrophils to tissues 38 . Consistent with these data, neutrophil numbers in the skin remained higher in nociceptor-deficient mice than in their control DTA littermates, suggesting that this persistent neutrophil influx plays an important role in the observed extensive skin damage.…”
Section: Discussionmentioning
confidence: 99%
“…associated with higher levels of chemokines and inflammatory cytokines, including CXCL1, which is known to attract neutrophils to tissues 38 . Consistent with these data, neutrophil numbers in the skin remained higher in nociceptor-deficient mice than in their control DTA littermates, suggesting that this persistent neutrophil influx plays an important role in the observed extensive skin damage.…”
Section: Discussionmentioning
confidence: 99%